The Blended Learning Model During Work from Home and Its’ Impact on Students’ Satisfaction and Learning Achievement in the Pandemic Covid-19 Period - rina nur hidayati rina nur hidayati; Faisal Ibnu Faisal Ibnu (International Journal of Nursing and Health Services (IJNHS), 2021)
The Covid 19 pandemic has caused many changes in various aspects of life, including education. This blended learning is the mixing of conventional (face-to-face) learning models with online learning. The study aimed to describe the blended learning model During Work From Home And Its' Impact On Students' Satisfaction And Learning Achievement In The Pandemic Covid-19 Period. A Cross-Sectional study approach was applied in this study. The samples were all students who took community nursing learning who selected using the purposive sampling technique. The researcher involved 121 students in this study. The data were collected using a questionnaire online via a google form. The results showed that most of the respondents were satisfied (60.3%), and their learning achievement was good (53.7%). Satisfied respondents will have good learning achievement as many as 44 respondents (60.3%). The p-value<0.05, which indicated that there is a relationship between satisfaction and learning achievement of respondents in community nursing learning. This study's results can provide input from the Ministry of Education and Culture, leaders of educational institutions, and teachers in making regulations and formulations for developing blended learning models, especially during the pandemic and in the Industrial Age 4.0